The Influance of Financial Performance Analysis on Stock Prices in Cement Sub-Sector Companies Listed on the Indonesian Stock Exchange for the Period 2017-2023 - Sari, Sri Nafika; Sam, Iskandar; Ridwan, Muhammad (Asian Journal of Management Analytics, 2025)
This study aims to investigate the effect of financial performance on the share price of companies listed on the Indonesia Stock Exchange (IDX). To achieve this goal, this study applies quantitative methods with multiple linear regression analysis. The data analyzed and used as a basis includes financial statements and company stock prices from 2017 to 2023. The results show that financial performance, as measured through various ratios such as Current Ratio (CR), Debt to Equity Ratio (DER), and Earnings per Share (EPS), has a significant influence on stock prices. This finding indicates that EPS contributes positively to stock price, while CR and DER show a negative impact. The conclusion of this study confirms that a company's financial performance has a great influence on its traded share price. Therefore, it is recommended that companies focus more on paying attention to and improving their financial performance, in order to encourage an increase in stock prices and strengthen investor confidence.